2022
DOI: 10.15252/embr.202255209
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic state prospectively identifies facultative stem cells in the intestinal epithelium

Abstract: The intestinal epithelium exhibits a rapid and efficient regenerative response to injury. Emerging evidence supports a model where plasticity of differentiated cells, particularly those in the secretory lineages, contributes to epithelial regeneration upon ablation of injury-sensitive stem cells. However, such facultative stem cell activity is rare within secretory populations. Here, we ask whether specific functional properties predict facultative stem cell activity. We utilize in vivo labeling combined with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In the intestine, we have recently demonstrated that high AV level prospectively identifies facultative stem cells that contribute to the DNA damage response after ionizing radiation exposure. 46 It remains to be determined whether facultative stem cells marked by high AV level contribute to esophageal response to stressors including 4NQO.
Figure 16 Proposed model.
…”
Section: Discussionmentioning
confidence: 99%
“…In the intestine, we have recently demonstrated that high AV level prospectively identifies facultative stem cells that contribute to the DNA damage response after ionizing radiation exposure. 46 It remains to be determined whether facultative stem cells marked by high AV level contribute to esophageal response to stressors including 4NQO.
Figure 16 Proposed model.
…”
Section: Discussionmentioning
confidence: 99%
“…There has been strong evidence that implicated EECs as facultative stem cells that promote plasticity and regeneration of the gut. 88 , 92 However, EEC expansion can also contribute to the rise of small intestinal neuroendocrine tumors. 93 EECs can revert to stem cells following injury with high intensity radiation (12 Gy) that causes massive cell death and ablation of crypt-based stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is further possible that 4NQO may promote a local microenvironment that activates the self-renewal potential of Cyto-ID High cells, similar to our findings in 3D organoids. In the intestine, we have recently demonstrated that high AV level prospectively identifies facultative stem cells that contribute to the DNA damage response following ionizing radiation exposure 44 . It remains to be determined if facultative stem cells marked by high AV level contribute to esophageal response to stressors including 4NQO.…”
Section: Discussionmentioning
confidence: 99%